The Influence of Educational Level, Family Economic Conditions, and Socio-Cultural Factors on Early Marriage in Wanasaba Subdistrict, East Lombok Regency - Kudusiah Kudusiah; Wahyunadi Wahyunadi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study is motivated by the persistently high incidence of early marriage in Indonesia, particularly in Wanasaba District, East Lombok Regency, despite the implementation of various governmental regulations and programs. This phenomenon has far-reaching implications for the educational, health, and socio-economic conditions of the community. The purpose of this research is to analyze the influence of educational attainment, family economic conditions, and socio-cultural factors on early marriage in Wanasaba District. The study employs a quantitative approach using a survey method and snowball sampling technique involving 60 respondents who married before the age of 19. Data were collected through closed-ended questionnaires using a Likert scale and analyzed through multiple linear regression. The findings indicate that educational attainment has a negative but statistically insignificant effect on early marriage (sig. 0.419), whereas family economic conditions and socio-cultural factors exert negative and significant effects (sig. 0.016 and 0.007, respectively). The simultaneous test yields a significance value of 0.005, demonstrating that the three variables collectively have a significant influence on early marriage, contributing 20.2% to the variation. These findings suggest that economic and cultural factors play a more dominant role than formal education; thus, efforts to prevent early marriage should focus on improving family welfare and fostering socio-cultural value transformation within the community.